Impact of premenstrual syndrome and premenstrual dysphoric disorder on adolescent and young women’s quality of life in northern India - Vishwakarma, Swati; Deo, Sujata; Mahour, Pooja; Jaiswar, S. P.; Agrawal, Monica (International Journal of Research in Medical Sciences, 2022)
Background: Our aim was to study the effect of PMS and PMDD on quality of life in adolescent and young women. Methods: This was a cross-sectional questionnaire based study was conducted from 2019 to 2020 in Department of Obstetrics and Gynecology, King Georges Medical University, Lucknow. After getting informed consent 358 female participant was enrolment. All participants were screened first according to PMS ACOG guideline then further DSM IV based premenstrual symptom screening tool (PSST) was applied by enquiring detail about last 3 menstrual cycles. The subjects which are diagnosed were given WHO-QOL-BREF scale. Results: The work efficiency or productivity, relationship with co-workers, relationship with your family, social life activities and home responsibilities were 27.63%, 26.31%, 22.36%, 15.78% and 15.13% in no/mild PMS, 94.73%, 86.84%, 73.68%, 60.52% and 42.10% in moderate to severe PMS and 100.00%, 85.71%, 57.14%, 42.85%, and 2.85% PMDD. The mean percentages of physical health domain were 64.43±8.29, 58.47±6.91, and 52.86±6.20; psychological health domain was 66.39±9.39, 62.47±7.73 and 56.29±4.64; social relationship domain was 62.29±12.45, 60.61±11.67 and 56.00±5.32 and environmental health domain was 64.52±9.64, 61.13±9.39 and 58.86±3.72 in no/mild PMS, moderate to severe PMS and PMDD participants group, respectively. Conclusions: The changes of physical health domain, psychological health domain were significantly negative correlated with moderate to severe PMS that means participant with moderate and severe PMS have poor quality of physical and psychological health whereas, social relationship domain and environmental health domain were also negative correlated but not significantly associated with moderate to severe PMS.